Reactive oxygen species contribute to oridonin-induced apoptosis and autophagy in human cervical carcinoma HeLa cells - Zhang Ya-hong; Wu Ying-liang; Tashiro Shin-ichi; Onodera Satoshi; Ikejima Takashi (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the role of reactive oxygen species (ROS) in oridonin-induced apoptosis and autophagy in HeLa cells. Methods: The cell viability was measured using MTT assay. Morphological changes of apoptosis and autophagy were examined using Hoechst 33258 staining and monodansylcadaverine (MDC) staining, respectively. The mitochondrial membrane potential (ΔΨm) was measured using fluorescent dye rhodamine 123. DCF-induced fluorescence was used to measure the intracellular ROS level. Protein expression was examined using Western blot. Results: Treatment of HeLa cells with oridonin (20–160 μmol/L) inhibited the cell growth in time- and concentration-dependent manners. The cells treated with oridonin (80 μmol/L) for 24 h displayed marked DNA fragmentation and MDC-positive autophagosomes. In the presence of the specific autophagy inhibitor 3-MA (2 mmol/L), the oridonin-induced apoptosis was significantly enhanced. Treatment of HeLa cells with oridonin (20–120 μmol/L) induced intracellular ROS generation in a concentration-dependent manner. In the presence of the ROS scavenger NAC (5 mmol/L), the oridinin-induced ROS generation was markedly reduced. NAC (5 mmol/L) or non-thiol antioxidant catalase (1000 U/mL) significantly reduced the oridonin-induced inhibition of cell growth and apoptosis. Furthermore, oridonin significantly reduced ΔΨm, which was blocked by NAC. Oridonin markedly increased Bax expression in mitochondria, and decreased Bcl-2 expression in both the cytosol and mitochondria. Oridonin also markedly increased the phosphorylation of Bcl-2 in the cytosol. All the effects were blocked by NAC. Oridonin increased the levels of caspase-3 and caspase-8, and decreased the expression of pro-caspase 3 and pro-caspase 9, which were blocked by NAC. Conclusion: ROS plays a critical role in oridonin-induced apoptosis and autophagy.